Quisinostat, bortezomib, and dexamethasone combination therapy for relapsed multiple myeloma. Issue 7 (2nd July 2016) - Moreau, Philippe; Facon, Thierry; Touzeau, Cyrille; Benboubker, Lotfi; Delain, Martine; Badamo-Dotzis, Julie; Phelps, Charles; Doty, Christopher; Smit, Hans; Fourneau, Nele; Forslund, Ann; Hellemans, Peter; et al.
Abstract: The maximum tolerated dose (MTD) of quisinostat + bortezomib + dexamethasone in patients with relapsed multiple myeloma was evaluated in a phase-1b, open-label, multicenter, '3 + 3' dose-escalation study. Patients received escalating doses of oral quisinostat (6 mg [ n  = 3], 8 mg [ n  = 3], 10 mg [ n  = 6], and 12 mg [ n  = 6] on days 1, 3, and 5/week) plus subcutaneous bortezomib (1.3 mg/m 2 ) and oral dexamethasone (20 mg) in cycles of 21 (cycles 1–8) or 35 d (cycles 9–11) until MTD was determined. No dose-limiting toxicities were reported in 6/8 mg groups except ventricular fibrillation (Grade 4 cardiac arrest, n  = 1 [10 mg] cycle 6) and clinically significant cardiac toxicities (Grade 3 QTc prolongation, Grade 3 atrial fibrillation, n  = 2 [12 mg]). Thrombocytopenia ( n  = 11), asthenia ( n  = 10), and diarrhea ( n  = 12) were most common adverse events. Overall, 88.2% patients achieved treatment response, median duration of response, and median progression-free survival were 9.4 and 8.2 months, respectively. The MTD of quisinostat was established as 10 mg thrice weekly oral dose with bortezomib + dexamethasone.